Incidence, Surgical Treatment, and Prognosis of Anorectal Melanoma From 1973 to 2011: A Population-Based SEER Analysis. Issue 7 (February 2016) - Chen, Haiyan; Cai, Yibo; Liu, Yue; He, Jinjie; Hu, Yeting; Xiao, Qian; Hu, Wangxiong; Ding, Kefeng
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Anorectal melanoma (AM) is a rare type of melanoma that accounts for 0.4% to 1.6% of total malignant melanomas. The incidence of AM increases over time, and it remains highly lethal, with a 5-year survival rate of 6% to 22%. Considering the rare nature of this disease, most studies on AM comprise isolated case reports and single-center trials, which could not provide comprehensive assessment of the disease. Therefore, we conducted a population-based study by using the Surveillance, Epidemiology, and End Results (SEER) program to provide the latest and best available evidence of AM. We extracted all cases of AM registered in the SEER database from 1973 to 2011 (April 2014 release) and calculated age-adjusted incidence. Only cases with active follow-up were included to predict factors associated with prognosis. Survival outcomes were also compared among different types of surgery. We identified 640 AM cases, which consisted of 265 rectal melanoma and 375 anal melanoma. The estimated annual incidence rates of AM per 1 million population were 0.259 in males and 0.407 in females, and it increased with advanced age and over time. Tumor stage and surgical treatment were independent predictors of survival. Results implied that surgery improved the prognosis of patients with local- and regional-stage AM but could not prolong the survival of patients with distant-stage AM. Moreover, the outcome of less extensive excision was not statistically different from that of more extensive excision. This study provides an up-to-date estimation of the incidence and prognosis of AM by using SEER data. The incidence of AM continuously increases over time, despite its rarity. This disease also exhibits poor prognosis. Thus, AM must be further investigated in future studies. We also recommend surgery as the optimal treatment for local- and regional-stage AM patients but not for those with distant metastasis.